1972
DOI: 10.1177/004051757204201207
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Pore Structure of Cotton by the Wet-Fixation Durable-Press Process

Abstract: Changes in the pore structure of cotton cellulose resulting from the steps of the wet-fixation process were assessed by measurement of moisture regain, water of imbibition, and dye sorption. These measurements reveal the relative proportions of pore surfaces in the nonswollen state, the pore volumes in the swollen state, and the pore surfaces in the swollen state, respectively. The uniformity of deposition of the methylolated melamine resin was established by both light and scanning electron microscopy; the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The slopes of the lines (structural diffusion resistance constants n) are not affected by dyeing temperatures. The solid lines in Figures 2,3,and 4 show the same logarithmic plots for LiOH mercerized, NaOH mercerized, and KOH mercerized cotton fabrics, respectively, and a similar tendency. ious cottons are ranked as follows: unmercerized fabric > KOH mercerized fabric > NaOH mercerized fabric > LiOH mercerized fabric.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The slopes of the lines (structural diffusion resistance constants n) are not affected by dyeing temperatures. The solid lines in Figures 2,3,and 4 show the same logarithmic plots for LiOH mercerized, NaOH mercerized, and KOH mercerized cotton fabrics, respectively, and a similar tendency. ious cottons are ranked as follows: unmercerized fabric > KOH mercerized fabric > NaOH mercerized fabric > LiOH mercerized fabric.…”
Section: Resultsmentioning
confidence: 54%
“…Part I of our study [ 13 ] showed that the swelling degree of the mercerized cotton affects the rate constant and the reaction state, but not the activation energy of the reaction between cellulose and crosslinking agent. Other studies [1][2][3][4][5][6][7][8][9][11][12][13][14] pointed out that crosslinking reduced the rate constant and equilibrium adsorption of dyeing.…”
mentioning
confidence: 99%
“…Those results strongly support the possibility that the crosslinking state and pore structure for DMDHEUaspartic acid might be different from that for DMDHEU. Many authors [4][5][6][7] have reported that the pore structures of the treated fabrics can be affected by varying the functional groups of crosslinking agents. However, detailed information about the pore structure for fabrics treated with DMDHEU-alpha-amino acids is lacking.…”
mentioning
confidence: 99%
“…Attempts to improve the balance of textile performance properties have centered on modifications in the chemical structure and location of crosslinks in the fabric assembly. In other papers, we have reported on the impacts of both crosslink structure [4,6] and crosslink distribution [2] on the moisture regain and water of imbibition of durable press fabrics. Moisture regain has been associated with internal fiber surface in the conditioned state, whereas water of imbibition is identifiod with internal fiber volume in a water swollen-state.…”
mentioning
confidence: 99%